Find Someone Who to Enhance Learning Outcomes in Speaking Skill - Sunaenah, Sunaenah (BAHTRA: Pendidikan Bahasa dan Sastra, 2023)
The main problem raised in this Classroom Action Research is the low English Learning outcomes achieved by grade VII students of Satap 1 Lingsar Elementary School in Speaking Skill in English. This research was carried out at SD-SMP Satap 1 Lingsar in grade VII of the 2022/2023 school year with a total of 36 students. This research is carried out in two cycles, each cycle in research includes four steps, namely (1) planning, (2) implementation (acting), (3) observation (observing), (4) reflection (reflecting). The results obtained in this study are: 1) Results in cycle I have an average value of 79, 2) Learning Completeness in cycle I of 78%, 3) Results in cycle II have an average value of 79, and 4) Learning Completeness in cycle II of 100%. Based on research data and discussion, it can be concluded that by applying the Find Someone Who Learning model to English subjects can Enhance classroom Learning outcomes